J. Basanavičiaus „Prakalba“ „Aušroje“ - Vėbra, Rimantas (Knygotyra, 1985)
The magazine „Aušra“ (The Dawn) – 1883–1886 – was the first Lithuanian periodical printed in Latin alphabet for Lithuania. It was a secular, illegal publication which served as a political mouthpiece for bourgeois patriots (who acted for the awakening of the national consciousness). Of great importance was the introductory article by J. Basanavičius published in the first issue of the periodical. In fact it outlined his ideological position. In this article we see J. Basanavičius as an ideologist of the burgeoning Lithuanian bourgeoisie. He put forward the call for equality of nations and formulated the main tasks of the Lithuanian society of his day. These were, 1) restitution of the rights and prestige of the Lithuanian language; 2) absolute necessity of establishing national schools and expanding secular education; 3) restoration of the people’s historical memory and learning from historical experience of the past; 4) raising and deepening of the national consciousness. These principles as well as others formulated by J. Basanavičius for the revival of the Lithuanian nation show his ideological maturity, his ability to see the main trends, to go to the very core of social phenomena. He founded the national ideology, gave an impetus for awakening and maturing the national consciousness; his ideas, although ideologically limited, were far from being neutral as might seem at first sight – in either a political or a social-economical sense. J. Basanavičius was in many respects a representative of the liberal democracy and his world outlook manifests an intricate pattern of educational and romantic ideas and some ideas and tendencies of positivism as well.